Optimizing Fructooligosaccharides Production from Beneng Taro (Xanthosoma undipes K.Koch) using Enzymatic Hydrolysis - Septariawulan Kusumasari; Tubagus Bahtiar Rusbana; Melva Debora Aritonang; Sri Mulyati (Politeknik Kesehatan Kemenkes Surabaya, 2026)
Fructooligosaccharides (FOS) are a prominent class of prebiotics that confer significant health benefits. Utilizing local resources like Beneng taro (Xanthosoma undipes K.Koch) for FOS production offers a sustainable strategy to enhance food security and add economic value to underutilized regional crops. This study investigated the potential of Beneng taro as a novel substrate for FOS production utilizing a crude inulinase preparation from Aspergillus niger, based on the hypothesis that optimizing enzymatic conditions can maximize FOS yield and polymerization quality. To systematically evaluate multi-factor interactions with minimal experimental runs, a D-Optimal Response Surface Methodology (RSM) was justified and employed. The experimental setup incorporated three independent variables (crude inulinase dosage, hydrolysis temperature, and hydrolysis time) with all trials performed in triplicate to ensure statistical robustness. The statistical model successfully predicted the optimal hydrolysis conditions, achieving 0.733 as desirability value. Verification experiments performed under these optimized conditions validated the model's predictive accuracy, yielding a high-quality product with the target total sugar, reducing sugar, and degree of polymerization. These findings demonstrate the viability of Beneng taro as a sustainable substrate for optimized prebiotic production, bridging local agricultural potential with functional food development.